2022
DOI: 10.3390/genes13101799
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Divergence between Toona ciliata and Toona sinensis Assayed with Their Whole Genome Sequences

Abstract: Toona ciliata and Toona sinensis belong to the Toona genus of the Meliaceae family and are important timber species in China. T. ciliata is an endangered species at level II due to overcutting and a low rate of natural regeneration. T. sinensis was cultivated as an economic and nutritious tree for more than 2000 years. The two species differ in flower and leaf morphological traits, reproductive systems, and range size of natural distribution. To reveal the potential molecular basis of these divergences, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Note that the large interval of the estimates of divergent times (Figure 4) could arise from the use of a wide range of divergent times derived from TimeTree database for calibrations (Kumar et al, 2017). This was the same situation for estimating the divergent times between T. ciliata and T. sinensis (Wang, Xiao, He, Li, Lv, Hu, et al, 2022;Wang, Xiao, He, Li, Song, et al, 2022). The fossil records are still lacking for the species that are closely related to the Toona genus.…”
Section: Evolutionary Divergence Among Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the large interval of the estimates of divergent times (Figure 4) could arise from the use of a wide range of divergent times derived from TimeTree database for calibrations (Kumar et al, 2017). This was the same situation for estimating the divergent times between T. ciliata and T. sinensis (Wang, Xiao, He, Li, Lv, Hu, et al, 2022;Wang, Xiao, He, Li, Song, et al, 2022). The fossil records are still lacking for the species that are closely related to the Toona genus.…”
Section: Evolutionary Divergence Among Varietiesmentioning
confidence: 99%
“…Here, we reported the phylogenetic relationships and the genetic differentiation among sympatric varieties with both the whole chloroplast genome sequence and markers, and explored the conservation strategy of this endangered species. Analysis with nuclear genomes will be present in a separate study using our recent assembly of nuclear genome sequences of T. ciliata as the reference genome (Wang, Xiao, He, Li, Lv, et al., 2022 ; Wang, Xiao, He, Li, Song, et al., 2022 ). One reviewer suggested inclusion of nuclear data analyses, but it is more appropriate to present the nuclear part in a separate study to accompany this work since more extensive analyses are needed with the resequencing data of these varieties.…”
Section: Introductionmentioning
confidence: 99%
“…This was similar with the expression pattern of PmFBPs in P. massoniana [ 18 ], while different from the expression pattern of HbcpFBPs in Hevea brasiliensis , with a higher expression level in bark than that in leaves [ 45 ]. The reason for the different tissue expression patterns of FBP gene may be caused by different plant species, as genomic differences are associated with differences in ecological adaptation [ 46 ]. The expression patterns of NcFBP4 and NcFBP5 were similar, except that the expression of NcFBP5 in green tissue was higher ( Figure 4 ), indicating that NcFBP5 may be chloroplast FBP, which was consistent with the previous evolutionary analysis ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the mating system scored by nuclear SSR markers indicated that the T. ciliata complex is predominantly outcrossing, with partial selfing and inbreeding [ 24 ]. Recent genome sequencing provides a useful reference for studying the phylogenetic relationship among varieties and for developing nuclear molecular markers for breeding [ 25 , 26 ]. All these studies provide a general picture of the genetic diversity and population structure of the T. ciliata complex, which serves as a valuable reference to the genetic conservation of this endangered species in China.…”
Section: Introductionmentioning
confidence: 99%